The impact of finanacial management reforms on operational effectiveness and accountability in Malaysian Central Government organisations - Karbhari, Yusuf; Mohamad, Muslim Har Sani (2005)

(untitled)
This study investigates the overall impact of financial management reforms undertaken by Malaysian central government organisations during the 1990s on operational effectiveness and accountability. The impact of the reforms on attitudes of staffs and planning was also discussed. The financial management reforms investigated in this study were the Modified Budgeting System, Internal Auditing System and Micro Accounting System. These reforms also shared characteristics of reform initiatives undertaken in developed countries including greater participation of line managers in managing public resources, output based performance contracts, and private sector accounting techniques. The findings of this study shed the light on the effectiveness of these programmes and disclosed the obstacles that undermined the reform objectives